From lab to field: biological control of the Japanese beetle with entomopathogenic fungi - Graf, Tanja; Scheibler, Franziska; Niklaus, Pascal A.; Grabenweger, Giselher (Frontiers in Insect Science, 2023)
The Japanese beetle Popillia japonica is an invasive scarab and listed as quarantine organism in many countries worldwide. Originating from Japan, it invaded North America, the Azores, and recently mainland Europe. The gregarious beetle threatens agriculture and horticulture by feeding on leaves, fruits, and flowers of a wide range of crops and ornamental plants. Larvae feed belowground and damage grassland. To date, no efficient and environmentally friendly control measure is available. Other scarab species are controlled using entomopathogenic fungi. In Switzerland, larval populations of Phyllopertha horticola and Melolontha melolontha are controlled by applying spores of Metarhizium brunneum and Beauveria brongniartii to larval habitats. Here, we aimed at adapting this control strategy to Japanese beetle larvae in grasslands, and testing spore spray applications against adults in crops. We carried out large-scale field experiments and inoculation experiments in the laboratory to assess the efficacy of registered fungal strains against Japanese beetle larvae and adults. Metarhizium brunneum established and persisted in the soil of larval habitats and on the leaves of adult’s host plants after application. However, neither larval nor adult population sizes were effectively reduced at the study sites. Laboratory experiments showed that larvae are not susceptible to two commercially available strains of M. brunneum and one of B. brongniartii, respectively. In contrast, adults were highly susceptible to all three strains. When injecting the spores directly into the hemolymph, both adults and larvae showed elevated mortality rates, which suggests that the cuticle plays an important role in explaining the difference in susceptibility of the two life stages. In conclusion, we do not see potential in adapting the state-of-the-art control of native scarabs to Japanese beetle larvae. However, adults are susceptible to all tested entomopathogenic fungi in laboratory settings and fungal spores survived high UV-radiation and heat for more than three weeks in the field. Hence, the control of adults with fungi of the genera Beauveria or Metarhizium is more promising than larval control. Further research on efficient application methods and more virulent and locally adapted fungal strains will help to increase efficacy of fungal treatments for the control of P. japonica.